Humoral immune response to COVID-19 vaccines in onchocerciasis-infected individuals: a field study from Ghana - Meyer, Julia; Klarmann-Schulz, Ute; Nadal, Jennifer; Parcina, Marijo; Debrah, Linda Batsa; Osei-Mensah, Jubin; Mensah, Derrick Adu; Ahiadorme, Monica; Opoku, Vera Serwaa; Obeng, Michael Agyemang; Kuutiero, Eunice Kyaakvile; Opoku, John; et al. (Frontiers in Immunology, 2025)
IntroductionCOVID-19 vaccines are the most successful medical interventions to reduce disease severity and mortality. Various vaccine platforms with unique properties have been developed. The course of the pandemic was contrary to the initial predictions, relatively mild in sub-Saharan Africa. Besides other contributing factors, helminths may also play a role due to their immunomodulatory properties. This study aimed to investigate antibody responses in onchocerciasis-infected individuals after multiple doses of different COVID-19 vaccines, comparing mRNA and vector-based vaccines, accounting for co-infections, and contrasting the findings with those from healthy endemic controls..MethodsFor this purpose, samples of onchocerciasis-infected individuals (n=110) from a larger and ongoing clinical trial were collected during the COVID-19 pandemic (December 2022) in northwestern Ghana. Participants were grouped according to their COVID-19 vaccine status as unvaccinated, incomplete (1 dose), and complete (2 doses). Helminth-specific and SARS-CoV-2-specific antibodies were quantified using ELISA, while a multiplex immunoassay was used to determine SARS-CoV-2 variant-specific neutralizing antibodies. Non-parametric statistical tests including Kruskal-Wallis and Mann-Whitney-U test were used for group comparison.ResultsThe data indicated a high SARS-CoV-2 seroprevalence among both, COVID-19 unvaccinated and vaccinated participants, despite the lack of a confirmed infection. Unvaccinated participants (n=44) showed 86% and 77% seropositivity for spike-specific IgA and IgG, respectively. Incompletely (n=22) and completely (n=36) COVID-19 vaccinated groups showed 63% and 50% nucleocapsid seropositivity, indicating viral exposure. The study identified elevated antibody levels following COVID-19 vaccination despite underlying onchocerciasis infection compared to the unvaccinated control group. However, comparable SARS-CoV-2 IgG levels were detected among mRNA and vector-based vaccinated individuals, as well as a higher breakthrough infection rate (NCP-seropositivity) in mRNA vaccinees. Interestingly, active-infected onchocerciasis individuals (Microfilaria positive) showed a reduced vaccine-induced IgG response after complete COVID-19 vaccination. Moreover, helminths may modify the vaccine- or infection-induced SARS-CoV-2 IgG subclass response, as the lack of IgG1 and the expression of IgG4 was associated with microfilaria and soil-transmitted helminth seropositivity.ConclusionThe study concluded that COVID-19 vaccines trigger a strong humoral immune response despite underlying onchocerciasis infection. However, parasitic status or microfilaria load may dampen vaccine-induced responses. These findings highlight the complexity of investigating vaccine responses in the presence of an undeterminable infection history, co-infections and polyparasitism in helminth-endemic areas and emphasize the need to further explore parasite-immunomodulatory mechanisms on COVID-19 vaccine efficacy for future vaccine development.